Ca2+/calmodulin‐dependent protein kinase II equally induces sarcoplasmic reticulum Ca2+ leak in human ischaemic and dilated cardiomyopathy. (8th September 2014) - Fischer, Thomas H.; Eiringhaus, Jörg; Dybkova, Nataliya; Förster, Anna; Herting, Jonas; Kleinwächter, Astrid; Ljubojevic, Senka; Schmitto, Jan D.; Streckfuß‐Bömeke, Katrin; Renner, André; Gummert, Jan; Hasenfuss, Gerd; et al.
<x xml:space="preserve">Abstract</x> Aims The sarcoplasmic reticulum (SR) Ca2+ leak is an important pathomechanism in heart failure (HF). It has been suggested that Ca2+/calmodulin‐dependent protein kinase II (CaMKII) is only relevant for the induction of the SR Ca2+ leak in non‐ischaemic but not in ischaemic HF. Therefore, we investigated CaMKII and its targets as well as the functional effects of CaMKII inhibition in human ischaemic cardiomyopathy (ICM, n = 37) and dilated cardiomyopathy (DCM, n = 40). Methods and results Western blots showed a significantly increased expression (by 54 ± 9%) and autophosphorylation at Thr286 (by 129 ± 29%, P < 0.05 each) of CaMKII in HF compared with healthy myocardium. However, no significant difference could be detected in ICM compared with DCM as to the expression and autophosphorylation of CaMKII nor the phosphorylation of the target sites ryanodine receptor 2 (RyR2)‐S2809, RyR2‐S2815, and phospholamban‐Thr17. Isolated human cardiomyocytes (CMs) of patients with DCM and ICM showed a similar frequency of diastolic Ca2+ sparks (confocal microscopy) as well as of major arrhythmic events (Ca2+ waves, spontaneous Ca2+ transients). Despite a slightly smaller size of Ca2+ sparks in DCM (P < 0.01), the calculated SR Ca2+ leak [Ca2+ spark frequecy (CaSpF) × amplitude × width × duration] did not differ between CMs of ICM vs. DCM. Importantly, CaMKII inhibition by autocamide‐2‐related inhibitory peptide (AIP, 1 µmol/L) reduced the SR Ca2+ leak by ∼80% in both aetiologies (P < 0.05 each) and effectively decreased the ratio of arrhythmic cells (P < 0.05). Conclusion Functional and molecular measures of the SR Ca2+ leak are comparable in human ICM and DCM. CaMKII is equally responsible for the induction of the 'RyR2 leakiness' in both pathologies. Thus, CaMKII inhibition as a therapeutic measure may not be restricted to patients suffering from DCM but rather may be beneficial for the majority of HF patients.